SENTIMENT ANALYSIS OF PUBLIC OPINION ON SOCIAL MEDIA X TOWARDS ETHNIC ROHINGYA IN INDONESIA - Ayu Amalia; Damayanti Damayanti (STMIK Royal, 2024)
Abstract: Rohingya refugees continue to arrive in Aceh by sea by boat. Based on data from the United Nations High Commissioner for Refugees (UNCHR), as of December 10 2023, 1,543 Rohingya refugees had landed in Aceh since mid-November 2023. The increasing number of refugees arriving has caused resistance from local residents. This rejection was the result of the bad experiences of Acehnese people with Rohingya refugees. The main problem of this research is that analyzing public opinion on Rohingya ethnicity in Indonesia is still done manually by looking at tweets one by one. The solution to overcome this is to analyze opinions using data crawling with the Naïve Bayes algorithm. The purpose of this research is to determine public opinion on Twitter media regarding refugee refugees. The method used in this research is the Naïve Bayes algorithm method. The results of the research show that the Naïve Bayes algorithm can classify public opinion sentiment on Twitter social media towards the Rohingya Ethnic in Indonesia into positive sentiment. and negative with a total accuracy of 70%. So, the words